The Cost of Corrosion in China - Hou, Baorong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book comprehensively covers corrosion and corrosion protection in China in the areas including infrastructure, transportation, energy, water environment, as well as manufacturing and public utilities. Furthermore, it presents a major consulting project of Chinese Academy of Engineering, which was the largest corrosion investigation project in Chinese history, including the corresponding methods, processes and corrosion protection strategies, and provides valuable information for numerous industries. Sharing essential insights into corrosion prediction and decision-making, this book will help to decrease costs and extend the service life of equipment and facilities; accordingly, it will benefit scientists and engineers working on corrosion research and protection, as well as economists and government employees.
Introduction of the study of corrosion status and control strategy -- Corrosion in the field of infrastructure -- Corrosion in the field of transportation -- Corrosion in the field of energy -- Corrosion in the field of water environment -- Corrosion in the field of manufacturing and public utilities.
Keywords: Coatings; Tribology; Corrosion and anti-corrosives.; Environmental management; Security systems; Buildings -- Repair and reconstruction; Buildings -- Maintenance; Coatings; Tribology; Corrosion; Environmental Management; Security Science and Technology; Building Repair and Maintenance